Combined aerobic and resistance exercise interventions for individuals with schizophrenia: A systematic review. (March 2017) - Martin, Heather; Beard, Samuel; Clissold, Nathan; Andraos, Kameel; Currey, Luke
Abstract: Introduction: Individuals with schizophrenia are more susceptible to cardiometabolic health risks due to increased sedentary behaviour. Exercise has been shown to modify cardiometabolic risk factors and mental health. We conducted a systematic review to identify effects of combined aerobic and resistance training on individuals with schizophrenia; and to aid the development of specific exercise guidelines. Methods: A systematic database search was conducted from inception until 09/16 for articles using combined exercise interventions measuring mental health variables, cardiovascular fitness or strength in individuals with schizophrenia. Of 2454 references, seven randomised control trials were eligible. Data extraction included outcome measures, study design, objectives, intervention, control, participants demographic, dropout, follow-up, study quality, and risk of bias. Results: Seven studies were eligible, involving 389 individuals with schizophrenia (mean age 38.7; 62% male) where 193 were assigned to intervention and 182 to control. Combined exercise was found to improve strength, symptoms of schizophrenia and overall mental health. Though improvements in cardiovascular fitness were not statistically significant they were still clinically meaningful. Program variables were poorly reported, however, interventions averaged approximately 95 min of aerobic exercise and strength training on 2 days per week at 50–85%1RM intensity. Research was scarce and overall, was of low study quality, with a high risk of bias. Conclusion: Combined exercise for individuals with schizophrenia is effective at improving strength and mental health variables. Current guidelines are adapted and non-specific for this population therefore development of specific guidelines should be a focus of future research. Highlights: Combined exercise is effective at decreasing symptoms of schizophrenia. Combined training increases muscular strength in people with schizophrenia. Cardiovascular fitness has clinically relevant increases with combined training. Rate of dropout and non-compliance is high in exercise interventions.